Manejo integrado del salta hojas (Perkinsiella saccharicida), en el cultivo de caña de azúcar (Saccharum officinarum - Rodriguez Briones, Dayana Isabel (2020)
This work seeks to contribute to the prevention and control of leaf hopping in sugar cane crops, since it is not only a part of Ecuador's economy and its international trade relations, but also in the diet of its inhabitants and because it generates sources of employment. The characteristics of leaf hopping and the damage it can cause the fungus that can be produced to the crop and the control methods that can be used will be discussed. Some producers consider it an unimportant pest but it can cause great losses in terms of yield because it attacks the leaf area of the plant. One of the controls that has no cost and is one of the lowest in leaf hopper population is the biological one. The form of attack of this insect begins from its state of nymph until it becomes an adult sucking the sap from the leaves causing weakness in the plants, yellowing of the leaves, low photosynthetic capacity and therefore low productivity.